Implementation of Policies To Eliminate Violence in Households in The Women's Empowerment Office and Child Protection of Hammer City - Muzakir Tawil; M. Kafrawi Al- Kafiah Samsu; Yulizar Pramudika Tawil; Risma Ariyani (Syntax Corporation Indonesia, 2023)
The Indonesian government has passed the Law on the Elimination of Domestic Violence (PKDRT Law) to provide comprehensive protection, including guarantees of legal protection and victim recovery. Domestic violence is stated in article 1 point 1 of Law Number. 23 of 2004 concerning the elimination of domestic violence. means any action against a person, especially women, which results in physical, sexual, psychological, and or domestic neglect, including threats to commit acts, coercion, or unlawful deprivation of independence within the scope of the household. Domestic violence can occur to husbands, wives, and children as well as those within the scope of the household. There are two main underlying causes of domestic violence. Firstly, economic factors. The economic factor in question is the lack of established economic conditions in the household so that the many demands that arise in the household are unable to be fulfilled. This condition is what then triggers conflict and even acts of domestic violence. Secondly, a patriarchal culture which embraces the meaning of a social system that places men as the main power holders and dominates in the role of political leadership, moral authority, social rights, and control of property. A patriarchal culture that sees paternal lineage indirectly gives birth to the idea that women have a lower position than men (subordinate). Which ultimately involves many women becoming victims of domestic violence. The objectives of this research are: To find out the implementation of the Domestic Violence Policy at the Palu City Women's Empowerment and Child Protection Office. The research design uses descriptive qualitative. This research is designed within one year